Intracranial Gliomas: Association between MRI Features and Tumor Grade (Bangladesh Journal of Neurosurgery, 2019)
Purpose: Intracranial gliomas are not uncommon in our country. The therapeutic management and prognosis in patients with gliomas depend on the reliable distinction between high and low-grade gliomas. The purpose of the present study was to determine whether any association exists between various individual MR imaging features and histopathologically determined tumor grade of intracranial gliomas. Our target was to explore whether MRI could enable correct determination the grading of gliomas which will help early diagnosis, staging, grade assessing, determining the appropriate treatment, preoperative planning for surgical resection and post operative management plan.Materials and Methods: It was a cross sectional type of observational study. This study was conducted on 44 cases of intracranial gliomas. Only patients having histopathologically proven intracranial gliomas who underwent surgery or stereotactic biopsy were considered as a study population.Results: The present study revealed that there is significant association between the MR imaging features and histopathological grading of intracranial gliomas. Contrast enhancement in MRI showed most significant (p